Adjunct ketamine treatment of depression in treatment‐resistant schizophrenia patients is unsatisfactory in pilot and secondary follow‐up studies. Issue 5 (15th March 2020) - Zhuo, Chuanjun; Lin, Xiaodong; Tian, Hongjun; Liu, Sha; Bian, Haiman; Chen, Ce
Abstract: Objective: To investigate the effects of adjunct ketamine treatment on chronic treatment‐resistant schizophrenia patients with treatment‐resistant depressive symptoms (CTRS‐TRD patients), including alterations in brain function. Methods: Intravenous ketamine (0.5 mg/kg body weight) was administered to CTRS‐TRD patients over a 1‐hr period on days 1, 4, 7, 10, 13, 16, 19, 22, and 25 of our initial pilot study. This treatment method was subsequently repeated 58 days after the start of the pilot study for a secondary follow‐up study. Calgary Depression Scale for Schizophrenia (CDSS), Positive and Negative Syndrome Scale (PANSS), and regional homogeneity (ReHo) results were used to assess treatment effects and alterations in brain function throughout the entire duration of our studies. Results: Between day 7 and day 14 of the first treatment, CDSS scores were reduced by 63.8% and PANSS scores were reduced by 30.04%. In addition, ReHo values increased in the frontal, temporal, and parietal lobes. However, by day 21, depressive symptoms relapsed. During the second treatment period, CDSS and PANSS scores exhibited no significant differences compared to baseline between day 58 and day 86. On day 65, ReHo values were higher in the temporal, frontal, and parietal lobes. However, on day 79, the increase in ReHo values completely disappeared. Conclusions: Depressive symptoms in CTRS‐TRD patients were alleviated with adjunct ketamine treatment for only 1 week during the first treatment period. Moreover, after 1 month, the antidepressant effects of ketamine on CTRS‐TRD patients completely disappeared. Correspondingly, ReHo alterations induced by ketamine in the CTRS‐TRD patients were not maintained for more than 3 weeks. These pilot findings indicate that adjunct ketamine treatment is not satisfactory for CTRS‐TRD patients. Abstract : Depressive symptoms in CTRS‐TRD patients were alleviated with adjunct ketamine treatment for only 1 week during the first treatment period. Moreover, after 1 month, the antidepressant effects of ketamine on CTRS‐TRD patients completely disappeared. Correspondingly, ReHo alterations induced by ketamine in the CTRS‐TRD patients were not maintained for more than 3 weeks. These pilot findings indicate that adjunct ketamine treatment is not satisfactory for CTRS‐TRD patients.